Truss joint with positive eccentricity experimental research = Badania eksperymentalne węzła kratownicy z mimośrodem dodatnim - Gordziej-Zagórowska, Małgorzata; Urbańska-Galewska, Elżbieta; Deniziak, Patryk; Pyrzowski, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the technological reasons in modern lightweight steel trusses, fabricated from cold-formed sections, positive eccentricities appear in the truss nodes what induce additional forces in the truss chords. To account for the real load-carrying capacity of truss node area the steel structure research in scale 1:1 were conducted.
Keywords: steel structures; thin-walled structures; cold-formed sections; eccentricities; truss; experimental research; konstrukcje stalowe; konstrukcje cienkościenne; kształtownik gięty na zimno; mimośrody; kratownice; badania eksperymentalne